Effect of composition and grain size on dielectric, ferroelectric and induced strain behavior of PLZT/ZrO2composites - Narit Funsueb (2018)
© 2018 Elsevier Ltd and Techna Group S.r.l. Lead lanthanum zirconate titanate ceramics (PLZT) are well known for their excellent dielectric, piezoelectric and ferroelectric properties. In this study, PLZT 9/70/30, 9/65/35 and 9/60/40 ceramics were prepared by vibro-milling mixed-oxide method. All compositions of powders were uniaxial pressed in pellets and sintered at the temperatures of 1200–1275 °C with various soaking times of 2, 4 and 6 h. The X-ray diffraction (XRD) patterns confirmed that all the PLZT samples had perovskite structure with ZrO2as a second phase and PLZT/ZrO2composite structure was formed. Dielectric behavior at the frequency of 1 kHz showed broad peak indicating relaxor ferroelectric behavior and the difference of the temperature at maximum dielectric at different frequencies increased when Zr:Ti ratio increased. Polarization with electric field (P-E loop) at room temperature showed that when Zr:Ti ratio increased, the coercive field decreased resulting from crystal structure change from tetragonal to rhombohedral. Induced strain with electric field depended on microstructure where the value of Smax/Emaxtended to decrease with increasing grain size. It can be concluded that dielectric and ferroelectric behavior predominantly depended on composition of PLZT ceramics and induced strain behavior predominantly depended on grain size of PLZT ceramics.